Superior one-pot synthesis of a doped graphene oxide electrode for a high power density supercapacitor. (6th June 2018) - Duraivel, Malarkodi; Nagappan, Saravanan; Balamuralitharan, B.; Selvam, S.; Karthick, S. N.; Prabakar, K.; Ha, Chang-Sik; Kim, Hee-Je
Abstract : The facile one-pot synthesis of sulfur-doped reduced graphene oxide results in a high powder density and easily reproducible electrode material. Abstract : In this work, we report the synthesis of sulfur-doped reduced graphene oxide (S-rGO) using sodium borohydride (NaBH4 ) and sodium sulfide (Na2 S) by a facile one-pot approach via refluxing in deionised water. The undoped rGO chemical structure is partially reduced by NaBH4, whereas the addition of a small amount of Na2 S with NaBH4 resulted in a better reduction of rGO. XPS analysis confirmed the successful doping of sulfur and Raman spectroscopy verified the increased defect density. The S-rGO electrode exhibits good power density (3202 W kg −1 ) with increased specific capacitance (392 F g −1 ) and cyclic stability (91%, 2000 cycles) in 1 M Na2 SO4 aqueous electrolyte. The obtained results suggest that the simple tuning of the graphene oxide structure using Na2 S with NaBH4 enhances the above properties. Moreover, this method is facile and allows the easy reproduction of bulk quantities of materials for use in commercial applications.